Flavonoids affect the endophytic bacterial community in Ginkgo biloba leaves with increasing altitude - Fu, Shaodong; Deng, Yan; Zou, Kai; Zhang, Shuangfei; Liu, Xueduan; Liang, Yili (Frontiers in Plant Science, 2022)
Altitude affects plant growth and metabolism, but the effect of altitude on plant endophytic microorganisms is still unclear. In this study, we selected 16 Ginkgo Biloba trees to study the response of leaves' endophytes to flavonoids and altitude (from 530 m to 1300 m). HPLC results showed that flavonoids in Ginkgo Biloba leaves increased by more than 150% with attitude rising from 530 m to 1300 m, which revealed a positive correlation with altitude. Ginkgo Biloba might regulate the increased flavonoids in leaves to resist the increasing light intensity. 16S rDNA sequencing results showed that the endophytic bacterial communities of Ginkgo Biloba at different altitudes significantly differed. The alpha diversity of Ginkgo endophytes decreased with increasing flavonoids content and altitude. The increased flavonoids content might increase the environmental pressure in Ginkgo Biloba and regulate the growth of some microorganisms. With the increase of flavonoids, the enrichment of microorganisms such as Clostridium also verified this speculation. The bacterial network in ginkgo leaves became more complex with increasing altitude, validating this conclusion. Metagenomes results predicted with PICRUSt showed that the abundance of flavonoid biosynthesis and photosynthesis genes were significantly decreased with the increase of flavonoid contents. High flavonoid content in leaves appeared to inhibit microbial flavonoid synthesis. Our findings indicate that altitude can modulate microbial community structure through regulating plant metabolites, which is important to uncovering the interaction of microbes, host and the environment.